(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The reading comprehension process is a complex mental process based on cognitive and metacognitive processes that start from decoding written words, sentences and paragraphs, to examining the text, appreciating it and expressing an opinion on it by investing in the skills of analysis, synthesis, inference and evaluation, passing through the processes of understanding explicit and implicit meanings that form the first nucleus for building the mental lexicon as a mechanism for language acquisition and learning. Given the importance of the latent relationship between building the lexicon and developing reading comprehension skills at an early age, this research paper came to present the most important suggestions to help the learner in Moroccan primary school to internalize vocabulary and its meanings with the aim of enriching his linguistic repertoire and facilitating his explicit and implicit reading comprehension and improving his lexical and communicative competencies; starting from the learner’s true reading comprehension level, which we will reveal by conducting a set of evaluation tests, in order to ensure the maximum effectiveness of educational suggestions. Using field research that makes sixth-level learners a sample for the research.